High temperature-induced plant disease susceptibility: more than the sum of its parts. (August 2020) - Cohen, Stephen P; Leach, Jan E
Abstract : Higher temperatures associated with climate change often increase the severity of plant diseases. An understanding of how plants respond to pathogens during high temperature stress is required for crop improvement, but the molecular mechanisms underlying this response are largely unknown. Mechanistic research has primarily focused on plant responses during either single stresses or heat-induced loss of single gene resistance. Transcriptome analyses of plant responses to a single stress compared to combined-stresses reveal significant differences showing that single-stress response studies are inadequate for determining the mechanisms of high temperature-induced disease susceptibility. To combat plant disease in light of climate change, future research will require comprehensive study designs and analyses.